Teaching of Arabic vocabulary in the French schools in Morocco: Some didactic proposals - Amehdar, Abdelmajid (Anaquel de Estudios Árabes, 2020)
Studies of the teaching of Arabic vocabulary in the French schools in Morocco. To do this, we will discuss the advantages and disadvantages of using a bilingual dictionary in class. Then, the importance of memorization, organization and presentation of lexical contents will be explained based on the existing theories on the teaching of second languages. This procedure will allow us to know what are the most significant tasks to develop effectively the lexical competence of users.
Keywords: arabic; lexical wealth; memorization; organization; classification; presentation